Indications for transfusion of donor blood components in emergency surgery - E. N. Kobzeva; E. A. Sakharova; B. A. Sorokin; V. B. Khvatov (Трансплантология (Москва))
In terms of complications due to allogeneic blood transfusions, it is necessary to use the latter only in accordance with the strict indications elaborated specifically for each component. When indications for the use of red blood cell-containing media are substantiated, it is essential to take into account not only laboratory data and transfusion trigger compliance, but also the clinical picture of hemic hypoxia. While prescribing fresh frozen plasma, one should be based on laboratory coagulogram readings.